Variability of motor moment during golf swing: study of a female professional player - Bourgain, M.; Provot, T.; Sauret, C.; Valdes-Tamayo, L.; Rouillon, O.; Thoreux, P.; Rouch, P. (Computer Methods in Biomechanics and Biomedical Engineering, 2020)
Golf swing performance has been widely studied. Performance parameters based on various mechanical concepts were developed such as X-factor (Kwon et al. 2013), or ground reaction forces (McNitt-Gray et al. 2013), for instance. More recently, parameters based on the capacity to generate motor moments were introduced (Bourgain et al. 2017) to better describe performance.